Development And Implementation Of Post Graduate Nuclear Engineering Education In Nigeria - Ayoade Kuye; Franklin Osaisai (International Journal of Nuclear Security, 2016)
Nigeria has abundant energy resources that include natural gas, large hydro, coal, nuclear, small hydro, solar (PV and PT), and wind. However, the country's per capita electricity consumption is lower than the African continent’s average. Therefore, there is a need for the diversification of the electricity supply in Nigeria. The government of the Federal Republic of Nigeria has acknowledged that nuclear energy would play a significant role in enhancing the per capita electricity generation. Consequently, the Nigeria Atomic Energy Commission (NAEC), as the national focal agency for developing and harnessing peaceful uses of nuclear energy in Nigeria, developed a strategic plan for the implementation of nuclear energy known as the National Nuclear Power Programme (NNPP). The NNPP plan was approved by the federal government of Nigeria in 2007. A critical component of the NNPP is the construction and operation of a nuclear power plant. Nuclear power plants are huge national engineering assets that require a plethora of human resources. In order to meet this need for knowledgeable and capable individuals, the NAEC, in partnership with four Nigerian universities, developed a curriculum for master’s programs in nuclear science and engineering. This paper discusses the master’s program in nuclear engineering that was implemented at the University of Port Harcourt. The program lasts for 15 months and consists of 20 core courses, 4 electives, and one research project. To date, 13 students have graduated from the master’s program and acquired the necessary competencies with three of these graduates already enrolled in PhD programs for nuclear engineering outside Nigeria. In addition, nine papers have been published in international journals from the research work carried out by these students
Keywords: Nuclear Engineering; Curriculum Development; Engineering Education